Environmental Policy Implementation in West Java (Studies in the Ciletuh Geopark Tourism Area) - Iwan Henri Kusnadi (Universitas Sultan Ageng Tirtayasa, 2023)
The tourism industry is an important aspect of economic growth; therefore, this sector continues to experience demands for expanding development. But unfortunately, often the logic offered by tourism does not meet the logic of the environment, so in many cases the environment becomes a victim. This situation prompted researchers to look at how environmental justice operates in tourism policy at the UNESCO Global Geopark Ciletuh (UGGC). This research uses policy implementation theory from George Edward III and environmental justice theory from Taylor. Methodologically, this research uses the descriptive-qualitative method. The results of the study reveal that from the four theoretical indicators, namely communication, resources, organizational structure, and disposition, it is clear that the implementation of environmental policies is still experiencing obstacles. This is caused by human resources, both managers and local residents, who have not been able to understand the concept of geopark ecology and the value of environmental justice. In the technical realm, environmental policy implementers are still stuttering and nervous about translating ecological rights into tourism operations in Ciletuh. Ciletuh has a big challenge in terms of ecology if policy implementation is still not able to understand the principles of environmental justice.